## Ask Singapore Homework?

Upload a photo of a Singapore homework and someone will email you the solution for free.

## Question

secondary 4 | E Maths

Anyone can contribute an answer, even non-tutors.

##### Anonymous

chevron_right chevron_right

Help pls!

Date Posted: 4 months ago
Views: 31
J
4 months ago
2x² - 6x - k = 0

Sum of roots

= -(-6)/2
= 3

Since roots differ by 5,

First root = second root + 5

Sum = first root + second root
= Second root + 5 + second root
= 2 x second root + 5

2 x second root + 5 = 3

So 2 x second root = 3 - 5 = -2

Second root = -2 ÷ 2 = -1
First root = -1 + 5 = 4

(You can also use first root = second root - 5. The roots will just swap places.

i.e first root will then be -1 and second root will be 4 )

Product of roots
= -k/2= 4 x (-1) = -4

k/2 = 4
k = 2 x 4 =

To check (if you wanna be sure. Or you can also use this as the alternate working for finding k)

x = 4 or x = -1
x - 4 = 0 or x + 1 = 0

So since they are the two roots,

(x - 4)(x + 1) = 0

x² - 3x - 4 = 0

2x² - 6x - 8 = 0

k = 8

### See 1 Answer

done {{ upvoteCount }} Upvotes
clear {{ downvoteCount * -1 }} Downvotes